Managing a transboundary pest: the fall armyworm on maize in Africa - Otim, M.H.; Fiaboe, K.; Akello, J.; Mudde, B.; Obonyom, A.T.; Bruce, Anani Yaovi; Opio, W.A.; Chinwada, P.; Hailu, A.; Paparu, P. (IntechOpen, 2021)
The fall armyworm (Spodoptera frugiperda J.E Smith) (Lepidoptera: Noctuidae) invaded Africa in 2016, and has since spread to all countries in sub-Saharan Africa, causing devastating effects on mainly maize and sorghum. The rapid spread of this pest is aided by its high reproductive rate, high migration ability, wide host range and adaptability to different environments, among others. Since its introduction, many governments purchased and distributed pesticides for emergency control, with minimal regard to their efficacy. In this chapter, we review efforts towards managing this pest, highlight key challenges, and provide our thoughts on considerations for sustainable management of the pest.